A Case of Multiple Intratumoral Hemorrhage and Rupture of Hepatocellular Carcinoma after Starting Lenvatinib. (19th December 2020) - Ishihara, Katsutoshi
Abstract : A man in his 80s was administered lenvatinib to treat multiple hepatocellular carcinomas. After starting lenvatinib, he was admitted to our hospital for fever and epigastric tenderness. Conjunctival icterus and conjunctival pallor were observed. Computed tomography showed high density areas in his tumors which were suggestive of intratumoral hemorrhage and tumor rupture. As a result, the patient underwent an emergent angiography and arterial embolization.